The Oxford Handbook of Positive Psychology 2009
DOI: 10.1093/oxfordhb/9780195187243.013.0018
|View full text |Cite
|
Sign up to set email alerts
|

Flow Theory and Research

Abstract: This chapter describes flow, the experience of complete absorption in the present moment, and the experiential approach to positive psychology that it represents. We summarize the model of optimal experience and development that is associated with the concept of flow, and describe several ways of measuring flow, giving particular attention to the experience sampling method. We review some of the recent research concerning the outcomes and dynamics of flow, its conditions at school and work, and interventions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
475
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(494 citation statements)
references
References 0 publications
9
475
0
10
Order By: Relevance
“…A flow experience occurs when one is engaged in a challenging activity that matches one's skill level (Csikszentmihalyi and Hunter 2003). Being in a flow state has been described as having an out-of-body experience in which nothing else matters except what one is doing at that very moment (Nakamura and Csikszentmihalyi 2009). Although people are typically not selfaware during flow, they report afterwards that their experience had been intensely positive.…”
Section: The Importance Of Need Satisfaction and Flowmentioning
confidence: 99%
“…A flow experience occurs when one is engaged in a challenging activity that matches one's skill level (Csikszentmihalyi and Hunter 2003). Being in a flow state has been described as having an out-of-body experience in which nothing else matters except what one is doing at that very moment (Nakamura and Csikszentmihalyi 2009). Although people are typically not selfaware during flow, they report afterwards that their experience had been intensely positive.…”
Section: The Importance Of Need Satisfaction and Flowmentioning
confidence: 99%
“…In order to handle these tasks well and efficiently we need to focus our attention on them. Preferably we enter the state of flow, which means that we become fully immersed and focused on the task at hand [23]. However, when fully concentrated, we are less likely to pay attention to upcoming meetings and appointments [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained suggest the platform can be used by kindergarten children, who were found to enjoy using the system and had high levels of flow [20]. The instructors also reported that it was well accepted and praised its versatility as a supporting tool for their everyday classroom activities.…”
Section: Introductionmentioning
confidence: 85%
“…However, this feeling was mitigated once they were introduced to the robot and watched it move, where some smiles appeared and shyness was, in some cases, replaced by astonishment (this impression was also more frequent in girls). The overall impression was that children had high levels of flow, as defined by Nakamura and Csikszentmihalyi [20], i.e., the majority of them were fully immersed in a feeling of energized focus, full involvement, and enjoyment in the process of the activity with only 10.71% of boys and 9.38% of girls showing a lack of interest in the robot and the activity. In some cases, they tried to move the robot but failed in bringing the stick to the correct place where the RFID reader was located, but hardly any of the kids felt frustrated about this and continued in a mental state of flow, although boys seemed to enjoy the activity more.…”
Section: Emotional Issuesmentioning
confidence: 99%